The Effect of Aerobic Exercise and Macrothele raven Venom on Tumor-bearing Mice - Sheng, Z. J.; Qin, C. J.; Wei, C. W.; Miao, L. C.; Hua, Z. G.; Rui, C.; Lin, L.; Cai, W. M. (International Journal of Sports Medicine, 2015)
Liver cancer is one of the most common cancers in the world. Macrothele raven venom, a complicated mixture of neurotoxic peptides, proteins and low molecular weight material, has antitumor properties, but its mechanism of action is unknown. Moderate exercise has been shown to shrink tumors and cause a remarkable reduction in the tumor growth rate. In this study, we examined the antitumor effect of Macrothele raven venom in combination with exercise on tumor-bearing mice. Our results demonstrate that aerobic exercise in combination with venom administered at different doses was much more effective in a mouse H22 hepatoma model compared to separate administration of the 2 treatments. The underlying mechanism of this effect may be related to the expression of various tumor suppressor factors.
Keywords: aerobic exercise; Macrothele raven venom; tumor-bearing mice